Disseminating climate-smart livestock interventions in Uganda - Mugumya, Roland (International Livestock Research Institute, 2020)
Key activities of the Program for Climate-Smart Livestock (PCSL) project in Uganda include the establishment of greenhouse gas (GHG) emissions baselines, integration of adaptation and mitigation practices in livestock development and the development of Monitoring Reporting and Verification (MRV) protocols for reporting to the United Nations Framework Convention on Climate Change (UNFCCC).